Molecular and morpho-anatomical assessment of the family Dorididae (Mollusca, Nudibranchia) in the Mediterranean and North-East Atlantic - Renau, Mar F.; Salvador, Xavier; Moles, Juan (European Journal of Taxonomy, 2024)
In the present study, a revision of the phylogeny and taxonomy of the family Dorididae is carried out focusing on the genus Doris Linnaeus, 1758. The type species D. verrucosa Linnaeus, 1758 and a blueish and yellow morphotype of D. ocelligera collected in different localities in the Mediterranean Sea and the North-East Atlantic were sequenced, as well as D. bertheloti and the elusive D. marmorata for the first time. The genetic markers include the cytochrome c oxidase subunit I, 16S rRNA, and histone 3. The phylogenetic results suggest that the genus Doris is paraphyletic, and D. ocelligera morphotypes separate into two species, as confirmed with species delimitation tests. To complement the phylogenetic evidence with morphoanatomical data, the dissection of two specimens of each morphotype is conducted. Significant differences in morphological traits such as body shape, colouration patterns, and mantle tubercles come to light, together with anatomical differences in the relative shape and size of the radular teeth and reproductive structures. Considering the modern and old descriptions of D. ocelligera, it is finally concluded that the blueish morphotype belongs to D. ocelligera. In contrast, the yellow morphotype responds to the actual synonym Aldisa berghi (Vayssière, 1901), which is resurrected here as Doris berghi comb. rest. Considering the broad phylogeny of the family, some systematic notes at the genus level are here provided.